Pengaruh E-Service Quality dan Perceived Value terhadap Customer Satisfaction pada Aplikasi Mobile Bukalapak - Oswald Yokiman; Donant Alananto Iskandar; Prasetio Ariwibowo (Neolectura, 2021)
This research aims to find out the influences of e-service quality and perceived value on customer satisfaction. This research is a research with quantitative approach with a sample of 100 respondents who are Bukalapak users that already made purchases through Bukalapak Mobile Application at least 2 times, samples determined using nonprobability purposive sampling technique. Measurement used was questionnaire that was distributed through Google Form to respondents. The analysis data using SPSS 25. The result of this research shows that e-service quality significantly affect customer satisfaction with t value 6,112 > t table 1,98, perceived value significantly affect customer satisfaction with t value 5,310 > t table 1,98, e-service quality and perceived value significantly affect customer satisfaction silmutaneously with f value 86,815 > f table 3,09.